Digital Media Trends in Conflict Resolution Education: A Bibliometric Analysis of Primary School Research (2013–2023) - Wahyuningsih, Yona; Maftuh, Bunyamin; Darmawan, Deni (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study investigates the trends and thematic developments in digital media publications focusing on conflict resolution education in primary schools through bibliometric analysis. A total of 993 relevant articles published between 2013 and 2023 were analyzed using VOSviewer and Publish or Perish software. The findings identify three key thematic clusters: conflict resolution, digital media, and primary education. The study reveals a significant increase in publication rates from 2014 to 2017, followed by a marked decline in recent years, with only 18 articles published in 2023. Bibliometric mapping highlights the growing importance of digital tools, such as augmented reality and gamification, in facilitating conflict resolution education. Despite the decline in research interest, this study underscores the critical role of innovative digital media in addressing educational challenges and promoting harmonious learning environments. The findings provide a comprehensive reference for future research directions, advocating for the integration of advanced digital platforms to enhance conflict resolution skills among young learners and align with the demands of 21st-century education.